Perubahan Malonaldehida Hati, Bobot Relatif Bursa Fabricius dan Rasio Heterofil/Limfosit (H/L) Ayam Broiler yang Diberi Cekaman Panas - E Kusnadi (Faculty of Animal Science, Bogor Agricultural University, 2009)
The objective of the research was to determine the influences of heat stress and temperature-exposed time on liver malonaldehyde (MDA), relative weight of bursa fabricius and heterophil/lymfocite ratio of broilers. The research used 140 male broilers of 2 weeks of age. The treatments consisted of two factors. The first factor was five treatments: S1A (28.55?1.53 oC) with ad libitum of feeding, S1BT1 (S1 with pair feeding as S2A), S1BT2 (S1 with pair feeding as S3A), S2A (31.07?1.29 oC) with ad libitum of feeding and S3A (33.50?1.17 oC) with ad libitum of feeding. The second factor was five of temperature-exposed times (0, 4, 8, 16, and 32 days after treatments). Variables measured were liver MDA, relative weight of bursa fabricius and ratio of heterophil/lymphocite (H/L). The experiment used a completely randomized design in split plot (5x5), with 4 replications. The result indicated that liver MDA, relative weight of bursa fabricius and H/L ratio of S2 and S3 were higher than those of S1A, S1BT1 and S1BT2. H/L ratio of 4, 8, 16, and 32 days of temperature-exposed times were higher than that of 0 day. It was concluded that heat stress increased the liver MDA and H/L ratio, but decreased the relative weight of bursa fabricius. The temperature-exposed time increased the H/L ratio, but it did not affect the liver MDA and relative weight of bursa fabricius of broilers. Key words: heat stress, malonaldehyde, heterophil/lymphocite ratio, bursa fabricius, broiler